Association Between Aspirin Usage and Age-Related Macular Degeneration: An Updated Systematic Review and Meta-analysis - Yan, Ruijia; Zhao, Jing; Zhang, Xinai; Wang, Wei; Jiang, Zhengyao (Frontiers in Pharmacology, 2022)
Purpose: To investigate the association between long-term use of aspirin and age-related macular degeneration (AMD). Methods: An updated systematic literature search was conducted in PubMed, Medline, Cochrane Library, and Embase from conception to February 26, 2021, without any language restriction. All studies that evaluated the relationship between long-term aspirin use and AMD were included. Results: In the current study, 16 articles were pooled. Overall, no significant association was observed (estimate ratio=1.108, 95% confidence interval (CI): 0.886–1.385). When the subgroups were evaluated according to various standards, aspirin use was significantly correlated with AMD in studies with volunteer participants (estimate ratio=0.899, 95% CI: 0.830–0.974, P<0.01), studies followed up for >10 years (estimate ratio=2.206, 95% CI: 2.124–2.292, P<0.01), duration of aspirin use >10 years (estimate ratio=2.323, 95% CI: 2.234–2.416, P<0.01), and cohort studies (estimate ratio=1.961, 95% CI: 1.893–2.032, P<0.01). Conclusion: Therefore, the association of aspirin and AMD can be demonstrated with a long-term follow-up or aspirin use, appropriate study design and participant source. The findings in our study might provide practical information on intervention strategies.